FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN SABUN PADAT EKSTRAK BEKATUL BERAS MERAS (Oryza nivara L.) - Ni Luh Gde Mona Monika; Ni Made Suastini (Institut Teknologi dan Kesehatan Bintang Persada, 2024)
Red rice bran contains various secondary metabolite compounds. The phenolic compound content in red rice bran has high antioxidant activity which has the potential to be used in solid soap preparations to protect the skin from free radicals. The research aimed to formulate red rice bran extract into a solid soap preparation that has antioxidant activity. Extraction was carried out by maceration method using 96% ethanol solvent. The viscous extract obtained was subjected to phytochemical screening. Solid soap formulation with the addition of various extract concentrations of 1.5%, 2% and 2.5%. Antioxidant activity testing was carried out using the DPPH method. The research result showed that red rice bran extract had very strong antioxidant activity with an IC50 value of 18,164 ppm, then it can be formulated into soap preparations that have antioxidant activity. The highest antioxidant activity in solid soap preparations varied in concentration of 2.5% red rice bran extract (F3) with an IC50 value of 526.80 ppm, 2% concentration (F2) with an IC 50 value of 664.28 ppm, and the lowest in variations concentration of 1.5% (F1) with an IC 50 value of 5042.20 ppm. The physical quality characteristics of solid soap preparations from red rice bran extract (organoleptic characteristics, pH, free alkali, free fatty acids and foam height) met the requirement in accordance with SNI quality requirements for solid soap preparations.